2007
DOI: 10.1111/j.1460-2695.2007.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating fatigue sensitivity to polycrystalline Ni‐base superalloy microstructures using a computational approach

Abstract: A B S T R A C TA computational study is conducted to determine the influence of microstructure attributes and properties on driving forces for fatigue crack formation and microstructurally small crack growth in a polycrystalline Ni-base superalloy, IN100, a turbine disk alloy. A principal objective is to obtain quantitative estimates of the effect of variability of microstructure features on scatter in fatigue life or fatigue strength for a given life. Understanding is sought regarding sensitivity of driving f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 39 publications
1
125
0
Order By: Relevance
“…In connection with the former, independent experimental and crystal plasticity computational studies in ferritic steel samples have indicated the importance of stored energy density (is Jm -2 ) in determining both the location of crack nucleation, and in predicting cycles to nucleation [14]. The stored energy, it is argued, accrues by virtue of the establishment of sessile dislocation structures of both geometrically necessary and statistically stored types, both of which have been incorporated in determination of stored energy in dislocation-based crystal plasticity models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In connection with the former, independent experimental and crystal plasticity computational studies in ferritic steel samples have indicated the importance of stored energy density (is Jm -2 ) in determining both the location of crack nucleation, and in predicting cycles to nucleation [14]. The stored energy, it is argued, accrues by virtue of the establishment of sessile dislocation structures of both geometrically necessary and statistically stored types, both of which have been incorporated in determination of stored energy in dislocation-based crystal plasticity models.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews highlight the need to deliver new experimental insight into deformation processes and failure in fatigue to drive modelling that can accurately capture microstructurally-sensitive effects and use geometrically faithful models. These modelling efforts have focused at a range of length and timescales, using approaches such as molecular dynamic simulations [8,9] up to the grain level using crystal plasticity finite element techniques [10][11][12][13][14][15]. This range of approaches necessitates ever increasing fidelity of experimental studies that span length and timescales, such as X-ray synchrotron [16] [17,18] and high energy neutron diffraction [19]; as well as electron microscopy [20,21] microstructurally-sensitive and physically based modelling approaches necessitate local measurements of defect content and residual stresses to improve the prediction of fatigue crack nucleation and short crack growth.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold FIP, th , can be associated with the microscopic critical resolved shear stress threshold for yielding, τ y . The critical resolved shear stress may be estimated from the macroscopic yield via the Taylor relation σ y /M, where M = 3.06 is the Taylor factor for a randomly textured face-centered cubic (fcc) polycrystalline aggregate (Shenoy et al 2007). To estimate th , τ y is used in the modified form of the microstructurally small crack growth law given by Shenoy et al (2007) as…”
Section: Fatigue Damage Process Zonementioning
confidence: 99%
“…For the OFHC Cu, the magnitude of the burger vector b = 2.55 × 10 −10 m, η = 1, τ y = 13 MPa (McGinty 2001). A F S is calibrated such that the number of cycles for formation of a small crack is equal to the number of cycle for the growth of microstructurally small crack (MSC) at an applied strain level that is equal to the yield strain, ε y (Shenoy et al 2007). In Shenoy et al (2007), the MSC life is defined as the number of cycles for the crack to form and grow to 3 times the average grain size.…”
Section: Fatigue Damage Process Zonementioning
confidence: 99%
“…Furthermore, the mechanism of fatigue on a microscopic scale has been extensively investigated in many research studies by Mughrabi et al [21,22]. Furthermore, Shenoy et al [23,24] conducted a hierarchical model that provides the systematic linkage of the macroscale model to the microstructure. Steglich et al [25] investigated the micromechanical modelling of cyclic plasticity incorporating damage.…”
Section: Introductionmentioning
confidence: 99%